Phenomenology and classification of food behavior disturbances (literature review, part II) - V. V. Romatsky; I. R. Syomin (Бюллетень сибирской медицины)
Literature data on the epidemiological character concerning the occurrence of food behavior disturbances in the historical aspect are presented. Current diagnostic signs of this form of pathology are described, criteria of their improvement are discussed. The very high percentage of comorbidity of food behavior disturbances with psychic and somatic disorders is noticed by Russianand foreign authors.